Can Coetzees Michael K be called a Gandhian hero? (Stamford Journal of English, 2013)
Coetzees Life and Times of Michael K can be viewed as a novel of resistance. The title character Michael K, born with a physical deformity, refuses to submit to the situation he is subjected to. He withdraws himself from the world torn with an incomprehensible war. With a quest for a place free from bomb blasts, economic recession, colonized politics, and chaotic city life, Michael starts his journey for refuge. He finds it impossible because of intruding authority. Being tracked down and locked up with the rural guerrillas, he starts to live a life of invisible existence. Becoming a camp prisoner he refuses to take any kind of food. His refusal to eat reflects a kind of resistance. His resistance to the situation is not active, rather he resists in a very passive way. He does not offer any violent attempt and his resistance appears as non-violent and passive. Michaels passive resistance reminds one of Gandhis famous doctrine of passive resistance - Satyagraha. Gandhi preaches the philosophy of non-violent passive resistance, the concept of Satyagraha, as a forceful means of achieving socio-political goals without using violence. Michael K, living amid all, creates his own world, listens to the voice inside, and becomes the symbol of suffering. This paper explores whether Michael in any way embodies the principle of non-violent passive resistance against the authority. Stamford Journal of English; Volume 6; Page 90-102 DOI: http://dx.doi.org/10.3329/sje.v6i0.13905